Identification of a suitable internal control for fluorescence analysis on canine peripheral blood samples - Riondato, F.; Martini, V.; Poggi, A.; Rota, A.; Comazzi, S.; Sulce, M.; Bruno, B.; Borrelli, A.; Miniscalco, B. (Veterinary immunology and immunopathology, 2016)
•Stable internal controls are mandatory for fluorescence studies by flow cytometry.•We investigate the variability of expression of the main lymphoid antigens in dogs.•CD4 is highly stable and represents the best internal fluorescence control in dogs. Reliable detection of fluorescence intensity (FI) by flow cytometry (FC) is fundamental. FI depends on instrument settings and sample processing procedures: thus, measurements should be done using internal controls with known FI. Commercially available beads-based standards are expensive, thus reducing their usability in the veterinary practice. Cell subsets with stable mean FI (MFI) within the population have been proposed as acceptable surrogates in human medicine. In veterinary medicine, no data exist about stability of antigen expression among different subjects or upon sample storage. The aim of the present study was to evaluate MFI variability of main lymphocytes antigens among the lymphoid cells within each subject, among different subjects, and upon 24-h storage, in order to identify the antigen most suitable as stable internal control in MFI analyses. Peripheral blood samples from 18 healthy dogs were analysed by FC within 3h from sampling to assess the expression of CD3, CD5, CD4, CD8, CD21 and cyCD79b using conjugated monoclonal antibodies. Analyses were restricted to the lymphoid population. Fluorescent microbeads were added to each tube, and antigen MFI was calculated as Relative Fluorescence Intensity RFI (CD/beads). Fluorescence histogram CV (fhCV) for each CD was regarded as an index of the variability of expression among lymphocytes within each subject (cell-to-cell variability); whereas the CV of RFI was regarded as an index of inter-subjects variability (dog-to-dog variability). In 11 cases, FC analyses were repeated after 24h storage at 4°C and RFI and CVs of fresh and stored samples were compared to assess variability linked to storage. CD4 was identified as the best antigen to be used as an internal control for MFI analyses in canine peripheral blood samples because of low cell-to-cell and dog-to-dog variability, and optimal stability upon 24-h storage. Blood samples from a second group of 21 healthy dogs were labelled only with CD4, in order to assess the influence of breed, sex and age on the expression of CD4 in a larger case series. Based on univariate GLMs, none of these variables influenced CD4 RFI. Normalizing fluorescence data using lymphoid CD4 MFI as a reference would improve the comparison of results obtained by different laboratories, patients or times in diagnostic and research analyses of FI. Further studies are needed to confirm our results with different FC approaches.